Learning problem solving skills: Comparison of E-learning and M-learning in an introductory programming course - Malik S.I.; Mathew R.; Al-Nuaimi R.; Al-Sideiri A.; Coldwell-Neilson J. (Springer New York LLC, 2023)
Problem solving skills are considered an integral part of grasping the precise concepts of the programming domain for novices in introductory programming (IP) courses. But these skills are mostly covered only in early lectures of such courses or are included in just a few early chapters of some relevant textbooks. Consequently, high failure and dropout rates are often reported in IP courses. In this study, we developed and introduced an application, called PROBSOL, which is designed to focus on, and enhance, novice programmers problem solving skills. Two versions of the application were developed, a web-based version and a mobile app. The applications were based on pseudo-code techniques. A survey was implemented to collect students feedback and semi-structured interviews were conducted to collect instructors opinion about the applications. Moreover, final exam grades over two semesters were compared to determine the impact of including the PROBSOL applications in the course. The results show that both students and instructors appreciated the applications and that their use supports students cognitive gains and engagement. Moreover, they promote students affective engagement in the IP course. The use of the applications improves novices programming understanding, logic capabilities and problem solving skills. However, students preferred the mobile version rather than the web-based version during the course. The comparison of students grades showed that the students achievements were improved and attrition rates were reduced after introducing the PROBSOL applications in the course. 2019, Springer Science+Business Media, LLC, part of Springer Nature.